2020
DOI: 10.1016/j.heliyon.2020.e03241
|View full text |Cite|
|
Sign up to set email alerts
|

Annexin 2 protein expression is associated with breast cancer subtypes in African American women

Abstract: Background: A review of literature on the expression of Annexin 2 in cancer has shown that there is very limited research work on the association of this protein with breast cancer aggressiveness in African Americans. In the present study, TMA breast tissues from African American women were stained with Annexin 2 antibody to determine the association between the molecular subtypes and Annexin 2 protein expression. Method: An annotated case series of 135 breast cancer tissues archived from 2000 to 2010 was acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Annexin A2 (ANXA2) is a calcium-binding cytoskeleton protein located on the extracellular surface of endothelial cells and in various types of tumor cells [80]. It has been shown that the expression of ANXA2 in breast tumors can be a biomarker for predicting BC outcome in high-risk groups [81]. Chuthapisith reported that the proteins ANXA1 and ANXA2 are predictors of pCR, as it was demonstrated that the presence of ANXA2 in conjunction with ANXA1 could be a potential marker of non-pCR in BC [70].…”
Section: Proteomic: Proteins As Biomarkers Of Nac Response In Bc Patientsmentioning
confidence: 99%
“…Annexin A2 (ANXA2) is a calcium-binding cytoskeleton protein located on the extracellular surface of endothelial cells and in various types of tumor cells [80]. It has been shown that the expression of ANXA2 in breast tumors can be a biomarker for predicting BC outcome in high-risk groups [81]. Chuthapisith reported that the proteins ANXA1 and ANXA2 are predictors of pCR, as it was demonstrated that the presence of ANXA2 in conjunction with ANXA1 could be a potential marker of non-pCR in BC [70].…”
Section: Proteomic: Proteins As Biomarkers Of Nac Response In Bc Patientsmentioning
confidence: 99%
“…Serum-derived exosomes from AA women TNBC patients exhibited higher ANX2 expression compared to those from CA women. ANX2 is associated with the aggressiveness of breast cancer and is considered as a molecular marker for different breast cancer subtypes [ 95 ]. In addition, an overexpressed ANX2 AA cohort was also associated with poor overall survival and poor disease-free survival [ 96 ].…”
Section: Influence Of Genetic and Epigenetic Factors On Breast Canmentioning
confidence: 99%